IMPACT OF THE MOTORIZED PLOUGHING ON THE STRUCTURE OF TROPICAL FERRUGINOUS SOILS AND THE EFFICIENCY OF A CORN CULTURE (ZEA MAYS, L.) IN THE N’DALI TOWNSHIP IN NORTH-BENIN - Zokpodo, Koessi Lié Barnabé (My University, 2017)
Agriculture has an important role in the development of the Beninese economy. Now, the sector has a major change with the agricultural motorization. In order to contribute to the sustainable management of farms, this study evaluated the effect of four motorized ploughing depths on soil structure and vege - tative growth of maize. Results show that ploughing at 15 cm depth provides the best agricultural yield and does not adversely affect the physical, mechanical and hydrodynamic characteristics of the soil. The optimum yield is estimated at 2.98 t / ha with a plow depth of 14.66 cm for the DMR-ESR-W variety. The TZEE-W-SR variety was 3.29 t / ha obtained with a plow depth of 14.39 cm.
Keywords: Motorized ploughing; Ploughing depth; Tropical ferruginous soils; Agricultural yield; Benin.